等式两边同时乘以 (x-a)(x-b)(x-c)化简就得到了
为什么 1/(x-a)+1/(x-b)+1/(x-c)=0所以 (x-b)(x-c)+(x-a)(x-c)+(x-a)(
1个回答
相关问题
-
(x-b-c)/a+(x-c-a)/b+(x-a-b)/c=3 (x是未知数,1/a+1/b+1/c不等于0)
-
求lim [( a^x+b^x+c^x)/3]^(1/x) (a,b,c>0) x→0
-
集合A=﹛x|x²+x+a≤0﹜,B=﹛x|x²-x+2a-1≤0﹜,C=﹛x|a≤x≤6a-1﹜,集合A,B,C至少一
-
已知A={x丨a1x²+b1x+c1=0},B={x丨a2x²+b2x+c2=0}.
-
(1) 化简 (x-c)/(x-a)(x-b)+(b-c)/(a-b)(x-b)+(b-c)/(b-a)(x-a)
-
(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不等于零,求x-a-b-c
-
ax^+bx+c=0 x1+x2=-b/a x1*x2=c/a
-
X2+AX+B=0,X2+BX+C=0,X1+1=X,X2+1=X,求A+B+C
-
已知a/x + b/x + c/x =0,x/a + y/b + z/c =1 ,求证 x·x / a·a + y·y
-
(a-b+c+1)(a+b-c+1)=(x-y)(x+y) X=?Y=?